STRUKTURALISME LEVI STRAUSS SASTRA LISAN DELISERDAN - Nurelide Nfn (MEDAN MAKNA: Jurnal Ilmu Kebahasaan dan Kesastraan, 2019)
This research is a development research towards Deli Serdang legend invetarisation. The researcher analyzes two stories “ Sampuren Putih dan Gua Kemang (the white waterfall and Kemang Cave). This, theoritical concept used in this research is focusing on Claude Levi Strauss theory to discurs how Sampuren Putih and Gua Kemang Structures. Gua Kemang located Uruk rambutan known as Sembahe. Toward the story of Gua Kemang and Sampuren Putih are known the belief legend and supranatural legend, as the effect of Karonese who lived hear the locative are still believe on Supranatural things.